PEMIKIRAN MODERN DALAM ISLAM: JAMALUDDINAL-AFGHANI (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
PadatulisaninipenulisakanmembahastentangtokohpembaharuanModernklasikdalam Islam,disinipenulisakanmembahastentangJamaluddinAl-afghaniyangmerupakanpembaharuanpolitikdalamIslampadaabadkesembilanbelas,iaberupayameningkatkanstandarinteletualdanmoralumatislamdalammelakukansuatupembaharuan,namalengkapnyaadalahSayyidJamaluddinAl-Afghanibeliaulahirpadatahun1838M/1254H,beliaulahirdiAs’adabawilayahAfghanistan,tapiadapulayangmenyebutkanbahwaialahirdiwilayahPersia,padaumurnya12tahunbeliautelahhafalal-quran,danpadausiayangkedelapanbelastahunbeliautelahmenguasaiilmukeislamandanilmu-ilmuumumlainnya,danbeliaujugatelahbanyakmelakukanperjalanan,sehinggalebihmemantapkanilmuyangtelahiadapat,iajugasudahmampumenguasaiberbagaibahasa,sepertiArab,Afghanistan,TurkidanPersi